2020
DOI: 10.21203/rs.3.rs-34282/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Duodenal major papilla morphology can affect biliary cannulation and complications during ERCP, an observational study

Abstract: Background We investigated whether duodenal major papilla morphology could be a risk factor for failure of selective biliary cannulation (SBC) and post endoscopic retrograde cholangiography and pancreatography (ERCP) complications.Method A prospectively recorded database was reviewed retrospectively. Patients were included if they received therapeutic ERCP and had naïve major duodenal papilla. We used Haraldsson’s classification for papilla morphology, as follows: Regular (Type 1), Small (Type 2), Protruding o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
0
9
1
Order By: Relevance
“…In the present retrospective study, all of the ERCP procedures were performed by one experienced endoscopist, which may limit possible confounding factors resulting from the varying skill of the operators. However, patient factors, including abnormal duodenal papilla, twisting or stenosis of the distal bile duct, fast bowel motility, intradivertiucular or peridiverticular papilla and surgically altered anatomy, usually directly increase the operating difficulty, which may result in a decreased success rate (5)(6)(7)18,38). The present study found that preoperative normal serum bilirubin level was a risk factor that correlated with failure in a second ERCP (OR= 6.702, P= 0.034) by multivariate analysis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present retrospective study, all of the ERCP procedures were performed by one experienced endoscopist, which may limit possible confounding factors resulting from the varying skill of the operators. However, patient factors, including abnormal duodenal papilla, twisting or stenosis of the distal bile duct, fast bowel motility, intradivertiucular or peridiverticular papilla and surgically altered anatomy, usually directly increase the operating difficulty, which may result in a decreased success rate (5)(6)(7)18,38). The present study found that preoperative normal serum bilirubin level was a risk factor that correlated with failure in a second ERCP (OR= 6.702, P= 0.034) by multivariate analysis.…”
Section: Discussionmentioning
confidence: 58%
“…'Expert endoscopist' was defined as one having performed >1,000 ERCPs during their career and who could perform procedures equivalent to Grade 3 of the grading scale for the difficulty of ERCP, based on the ERCP core curriculum, without assistance (17)(18)(19)(20).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported the results of individual salvage techniques such as pre-cuts or compared 2 or 3 techniques in a limited small number of patients [5,[11][12][13][14][15][16][17][18][19][20]. There are also several studies analyzing the di cult factors of biliary cannulation [21][22][23][24][25]. On the other hand, no reports have clearly shown the stream of the procedure based on a particular strategy, which cases were di cult, and which salvage techniques were used successfully or not in all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported success rates and adverse events of each technique, although the analysis of all reports extracted only cases in which each salvage technique was performed [5,[11][12][13][14][15][16][17][18][19][20]. On the other hand, several articles have reported the factors that make biliary cannulation di cult in ERCP [21][22][23][24][25]. However, few of them have described how di cult cases were addressed using salvage techniques.…”
Section: Introductionmentioning
confidence: 99%
“…53 Small papillae are often more difficult to identify (discussed further below), especially when there is significant duodenal oedema, inflammation, or redundant mucosal folds, and thereafter cannulate. 54 A small papilla increases the odds of the sphincterotome coming in contact with the septum instead of insertion into the bile duct, especially if highly compressible, and may make it more difficult to make adjustments to the position of the sphincterotome without losing contact with the papilla. On the other hand, a large papilla may be more relaxed and floppy, providing less stability during cannulation.…”
Section: Patient Factorsmentioning
confidence: 99%